Między azylem dyplomatycznym a kanonicznym posłuszeństwem. Analiza prawna pobytu kardynała Józsefa Mindszentyego w placówce dyplomatycznej Stanów Zjednoczonych Ameryki - Fiejdasz-Buczek, Lidia; Szarek-Zwijacz, Anna (PRAWO i WIĘŹ, 2026)
The article provides a comprehensive analysis of Cardinal József Mindszenty’s stay at the United States diplomatic mission in Hungary, taking into account both international law and canon law perspectives. Drawing on unique beatification records and Vatican sources, the authors examine the Cardinal’s spiritual and moral motivations, emphasizing his fidelity to the norms of canon law, which played a decisive role in shaping his decisions and conduct. The text further addresses issues concerning the legal status of the diplomatic mission, the interpretation of the institution of diplomatic asylum, and the controversies surrounding its application in state practice. The analysis demonstrates that the resolution of the diplomatic impasse that gradually arose from the Cardinal’s long-term refuge at the U.S. diplomatic mission was facilitated by his heroic obedience to the Pope – a virtue that matured over the fifteen years of his presence at the American diplomatic mission.